Social Network as a Knowledge Service Provider - Mark, Shlomo; Tammy, Shalev; Shilon, Guy; Wolfson, Adi; Tavor, Dorith (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
One of the most important challenges facing humanity today is the design and development of more sustainable processes those that balance the needs of the present generation without compromising the ability of future generations to meet their own needs. The Sustainability as Service Science model (S^3) presents a novel perspective of the relationship between sustainability and services in the framework of service science by defining both sustainable services and sustainability as service and by describing the mutual relationship between sustainability and service. Information-rich, the field of sustainability in many ways suffers from information overload, which can foster uncertainty and confusion during any decision-making process. In this study we present a new social network framework, in which the social network is an ’information to knowledge’ service that shares knowledge, in the process evaluating its correspondence to and trustworthiness within the field of sustainability. Guided by the three basic principles of awareness, responsibility, and commitment, the new information to knowledge framework is conceptualized as a platform from which to transform the plethora of information available in the field of sustainability into practical and trusted knowledge.